Galeria bot: desenvolvimento de robô para inspeção de tubulações de águas pluviais - Savieto, João Adolfo [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Com o crescimento populacional anual, as cidades expandem sua infraestrutura, incluindo extensas redes de tubulações de águas pluviais, essenciais para o escoamento eficiente. No entanto, falhas de projeto, construção inadequada ou falta de manutenção podem gerar problemas estruturais significativos. A inspeção dessas tubulações é desafiadora devido ao difícil acesso e às condições de espaço confinado, exigindo equipamentos especializados ou expondo trabalhadores a riscos. Os métodos convencionais, geralmente baseados apenas em câmeras operadas remotamente, nem sempre fornecem informações suficientes para a tomada de decisões sobre reparos. Diante dessa limitação, este estudo propõe o desenvolvimento de um robô capaz de detectar e transmitir a posição de fissuras, medir o ângulo de declive e o comprimento da tubulação, além de empregar sistemas de segurança para evitar danos ao equipamento. A seleção criteriosa de componentes, como motores, rodas, sensores e microcontrolador, é essencial para o desempenho do robô, enquanto a navegação autônoma representa um desafio, dada a limitação do sinal GPS dentro das tubulações. Assim, foi implementado um sistema de navegação embarcado para fornecer a localização precisa das falhas. Testes práticos em um ambiente controlado demonstraram a eficácia do robô na identificação de fissuras e medições de inclinação por meio de sensores ultrassônicos e inerciais, com a aplicação de filtros complementares para fusão de dados. Os resultados indicaram conformidade com as normas de declive mínimo para escoamento (ABNT NBR 10844), além de precisão na detecção de fissuras, com variações mínimas em relação a instrumentos de referência. Como contribuição, este trabalho apresenta uma solução de baixo custo e fácil implementação, além de destacar melhorias futuras, como navegação autônoma, integração de sensores industriais e aumento da robustez para aplicações em campo.

With the annual population growth, cities expand in various sectors, particularly in infrastructure. A fundamental aspect to be analyzed is the stormwater drainage systems, which are responsible for the efficient runoff of water. Cities have kilometers of such pipelines, constructed over different periods to meet the demands of urban expansion. However, as frequently reported in the news, serious problems may arise when these pipelines are not designed or constructed properly, or whenWith annual population growth, cities expand their infrastructure, including extensive networks of stormwater pipelines essential for efficient drainage. However, design flaws, inadequate construction, or lack of maintenance can lead to significant structural problems. Inspecting these pipelines is challenging due to difficult access and confined space conditions, requiring specialized equipment or exposing workers to risks. Conventional methods, usually based solely on remotely operated cameras, do not always provide sufficient information for decision-making regarding repairs. Given this limitation, this study proposes the development of a robot capable of detecting and transmitting the position of cracks, measuring the pipeline’s slope angle and length, and employing safety systems to prevent equipment damage. The careful selection of components, such as motors, wheels, sensors, and microcontrollers, is essential for the robot’s performance, while autonomous navigation poses a challenge due to GPS signal limitations inside pipelines. Thus, an onboard navigation system was implemented to provide precise fault location. Practical tests in a controlled environment demonstrated the robot’s effectiveness in detecting cracks and measuring inclinations using ultrasonic and inertial sensors, with the application of complementary filters for data fusion. The results indicated compliance with the minimum slope standards for drainage (ABNT NBR 10844), as well as accuracy in crack detection, with minimal variations compared to reference instruments. As a contribution, this work presents a low-cost, easily implementable solution while highlighting future improvements, such as autonomous navigation, integration of industrial sensors, and increased robustness for field applications.
Bot gallery: development of a robot for stormwater pipe inspection
Keywords: Robôs; Análise; Inspeção; Precipitação (Meteorologia); Tubulações